A Simurelay-Supported Project-Based Jobsheet to Enhancing Learning Outcomes in Vocational Education - Elia Gustri; Asrul Huda (Postgraduate, University of Mataram, 2025)
Vocational education plays a crucial role in preparing skilled graduates to meet workforce demands. However, SMKN 1 Pariaman faces challenges such as low student motivation, poor learning outcomes, and a mismatch between teaching approaches and students’ dominant kinesthetic learning style. This study aims to develop a project-based learning (PjBL) jobsheet supported by Simurelay to improve the learning process in the subject of Electromechanical and Electronic Control Systems. Simurelay is utilized to help students understand practical concepts through simulation. The research follows a 4D development model—Define, Design, Develop, and Disseminate. The product was evaluated for validity, practicality, and effectiveness. The results indicate that the developed jobsheet is valid, practical, and improves student learning outcomes. This study concludes that a PjBL-based jobsheet assisted by Simurelay can effectively support practical learning in vocational education.